Exploring Time-Domain OFDM Signal Generation: Performance Analysis in Communication Systems - Tusin, Najwanisa; Joret, Ariffuddin; Abdullah, Mohammad Faiz Liew; Musirin, Ismail; Saon, Sharifah; Ponniran, Asmarashid; Sulong, Muhammad Suhaimi; Zakaria, Zahriladha (International Journal of Integrated Engineering, 2025)
Orthogonal Frequency Division Multiplexing (OFDM) is a method used to send multiple signals over a communications link where it can transmit subchannel frequencies closely spaced without overlapping. Furthermore, OFDM is a multicarrier modulation commonly used in telecommunication, especially in wireless communication systems such as the 4th Generation (4G) and Long-Term Evolution (LTE) due to its capability of providing some advantages in terms of data transmission. In a conventional OFDM system, the OFDM signal generation is made using complex input data represented in the frequency domain before being transformed into the time domain for transmission. This paper intends to explore the viability of generating the OFDM signal using a time-domain approach. This study then further assesses the processing performance of OFDM signal simulated as a communication system, in the frequency domain and the time domain by analyzing the Bit-Error-Rate (BER). In this study, Quadrature Amplitude Modulation (QAM) and Quadrature Phase Shift Keying (QPSK) were applied. The findings indicate that, the generated OFDM signal using the time domain method shows similar characteristics in terms of amplitude to those generated conventionally, specifically at , and for the time and frequency domain, respectively, when QAM is utilized. Meanwhile, using QPSK, at , the amplitude for the frequency and time domain are and . The error obtained between frequency and time domain are relatively small, and for QAM and QPSK, respectively. Besides, the BER value using QAM, at , is about for both time domain and frequency domain, which closely mirrors the theoretical BER. Similarly, for QPSK, at , BER is 0.0023, 0.0030, 0.0035 for the theoretical, time domain, and frequency domain, respectively. Based on the findings, the time-domain approach can be used in generating the OFDM signals and less complexity rather than the conventional, and the choice of domain does not introduce significant variances in the performance of the OFDM signal in communication system.